Effects of temperature on activities of antioxidant enzymes and Na+/K+-ATPase, and hormone levels in Schizothorax prenanti. (February 2018) - Yang, Song; Yan, Tao; Zhao, Liulan; Wu, Hao; Du, Zongjun; Yan, Taiming; Xiao, Qing
Abstract: This study evaluated the effects of temperature on the activities of antioxidant enzymes and hormone levels in Schizothorax prenanti. Schizothorax prenanti were acutely suffered from increasing temperature at a rate of 1 °C h −1 . The temperature started from 11 °C and the critical thermal maximum (CTMax) was measured to evaluated thermal tolerance of Schizothorax prenanti . Antioxidant parameters including superoxide dismutase (SOD), catalase (CAT), Na + /K + -ATPase and malondialdehyde (MDA) in gills, liver and muscle were measured at five temperature groups (11 °C, 16 °C, 21 °C, 26 °C and 31 °C). The plasma hormone including acetylcholine (ACh) and cortisol were also measured at five temperature groups. Our results showed that the CTMax of Schizothorax prenanti under acute heat stress was 31 °C.The activities of SOD and CAT in liver and muscle at 11 °C, 16 °C, 26 °C and 31 °C groups were significantly higher than 21 °C group, as well as Na + /K + -ATPase in gills and MDA concentrations in gills and liver. However, plasma ACh and cortisol levels were significantly increased with increasing temperature. The results indicate that oxidative stress parameters could respons to increase of temperatur, altogether reflect that Schizothorax prenanti has higher susceptibility of temperature. Thus, the effect of long-term high temperature on Schizothorax prenanti should be studied further. Highlights: The CTMax, antioxidant parameters (SOD, CAT, MDA and Na + /K + -ATPase) and hormone (ACh, cortisol) were determined to assess the heat stress capacity of Schizothorax prenanti . The Antioxidant parameters presented lowest in 21 ℃, which was the thermal optimum for Schizothorax prenanti .